2016
DOI: 10.1097/scs.0000000000002724
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Prophylactic Antibiotics in Nonoperative Facial Fractures

Abstract: Facial fractures are commonly managed nonoperatively. Patients with facial fractures involving sinus cavities commonly receive 7 to 10 days of prophylactic antibiotics, yet no literature exists to support or refute this practice. The aim of this study was to compare the administration and duration of antibiotic prophylaxis on the incidence of soft tissue infection in nonoperative facial fractures. A total number of 289 patients who were admitted to our level I trauma center with nonoperative facial fractures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…PAP with open reduction and internal fixation of facial fractures (ORIFfx) likely is unnecessary [6][7][8][9][10][11][12][13][14]. Despite these findings, a review from 2015 included a survey of US plastic surgeons that found that 75% employ PAP routinely for >24 hours, and the majority of respondents reported continuing antibiotic prophylaxis for at least one week [15].…”
mentioning
confidence: 99%
“…PAP with open reduction and internal fixation of facial fractures (ORIFfx) likely is unnecessary [6][7][8][9][10][11][12][13][14]. Despite these findings, a review from 2015 included a survey of US plastic surgeons that found that 75% employ PAP routinely for >24 hours, and the majority of respondents reported continuing antibiotic prophylaxis for at least one week [15].…”
mentioning
confidence: 99%
“…There remains controversy in the current literature regarding the benefits of prophylactic antibiotics in these patients, as good quality prospective data is lacking. [13][14][15] The treatment of these complex facial fractures can vary depending on several factors. These include the fracture pattern, degree of posterior table involvement, nasofrontal duct injury, neurological status, concomitant head injury, presence of CSF leak, and retinal detachment, which may preclude surgical access to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Protective equipment, in some cases, has reduced the frequency of catastrophic injuries. 7,15 Despite the growing medical and economic implications of pediatric traumas, 16 particularly craniofacial traumas, existing literature suffers from small sample sizes 4,17 and/or outdated data. 18 Additionally, many pediatric trauma studies restrict inclusion criteria to patients under the age of 18; yet postpubertal physiologic development may continue well into early adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic antibiotics are not prescribed routinely for patients with a nasal fracture or those undergoing MUA. Evidence has suggested a little benefit of prophylactic antibiotics in facial fractures overall, save for mandibular fractures 15. Likewise, the use of prophylactic antibiotics in nasal surgery is controversial, and typically only recommended if endonasal packing has been applied 16.…”
Section: Discussionmentioning
confidence: 99%